Some Preliminary Considerations for the Legal-Economic Analysis of Corporate Social Responsibility - Méndez Reátegui, Rubén; Tabra Ochoa, Edison (Universidad Hemisferios, 2021)
This review article presents some preliminary considerations and describes the evolution of corporate social responsibility, which is necessary for an informed study of this